Cyanin Chloride Inhibits Hyperbaric Pressure-Induced Decrease of Intracellular Glutamate-Aspartate Transporter in Rat Retinal Müller Cells - Chen, Xiaomin (J Ophthalmol, 2018)
PURPOSE: Glaucoma is the leading cause of irreversible blindness throughout the world. The pathogenesis of glaucoma is complex, and neuroprotection is a crucial aspect of therapy. High concentrations of extracellular glutamate are toxic to the optic nerve. The glutamate-aspartate transporter (GLAST) in retinal Müller cells is involved in the development of glaucoma. Anthocyanin has been reported to protect retinal neurons. We hypothesize that cyanin chloride, a type of anthocyanin, can inhibit hyperbaric pressure-induced GLAST decreases in cultured rat retinal Müller cells and may serve as a potential neuroprotective agent in glaucoma treatment. MATERIALS AND METHODS: Sprague Dawley rat Müller cells were cultured in a hyperbaric pressure device at 60 mmHg additional pressure and treated with cyanin chloride (10 μmol/L, 30 μmol/L, or 50 μmol/L) or vehicle for 2 hours. Cell survival rates (SRs) were evaluated by an MTT assay. GLAST mRNA and protein expression were determined by western blot and RT-PCR analyses, respectively. RESULTS: Cell SR was significantly decreased in the 60 mmHg additional hyperbaric pressure group compared to the control group (P < 0.01). Cyanin chloride treatment significantly improved SR under 60 mmHg additional pressure (P < 0.01). GLAST mRNA and protein expression levels in Müller cells were significantly reduced in the 60 mmHg hyperbaric pressure group compared to the control group (P < 0.01), but cyanin chloride significantly inhibited hyperbaric pressure-induced decreases in GLAST expression (P < 0.01). CONCLUSION: Our results support our hypothesis and demonstrate that cyanin chloride can protect rat retinal Müller cells from hyperbaric pressure-induced decreases of GLAST.